Answered

Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Solve a system by substitution method. 

X + 2y = 6
3x - 2y = 2

Help...?


Sagot :

you have to set one of the equations equal to one of the variables.  Easiest one would be using the top equation. SO
x=6-2y
then substitute 6-2y in the 2nd equation for the x. SO
3(6-2y)-2y=2
18-6y-2y=2
18-8y=2
-8y=-16
y=2
so you know what y is you can plug in the value of it to find x
3x-2(2)=2
3x-4=2
3x=6
x=2

x=2 and y=2
you can check your answers to see that it is correct

Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.